9x-2=4x-9

Simple and best practice solution for 9x-2=4x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-2=4x-9 equation:


Simplifying
9x + -2 = 4x + -9

Reorder the terms:
-2 + 9x = 4x + -9

Reorder the terms:
-2 + 9x = -9 + 4x

Solving
-2 + 9x = -9 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-2 + 9x + -4x = -9 + 4x + -4x

Combine like terms: 9x + -4x = 5x
-2 + 5x = -9 + 4x + -4x

Combine like terms: 4x + -4x = 0
-2 + 5x = -9 + 0
-2 + 5x = -9

Add '2' to each side of the equation.
-2 + 2 + 5x = -9 + 2

Combine like terms: -2 + 2 = 0
0 + 5x = -9 + 2
5x = -9 + 2

Combine like terms: -9 + 2 = -7
5x = -7

Divide each side by '5'.
x = -1.4

Simplifying
x = -1.4

See similar equations:

| -7y=6y+1 | | 9(x+1)=6(x-1) | | 16+0.08x=0.1(100+x) | | x-11=x+9 | | 3z+2(z-9)= | | 2(2n+5)=6(6n+1)+5 | | 84=-2n | | 4x-81=x+3 | | 2(3.14)60+2(3.14)25=S | | 14x+28=12x+4 | | 10r-6r+7=7r+7-r | | 7(7y-4)= | | -3+5=-8x-7 | | (3a+4)-(5a-2)=7 | | y+1.4=8.4 | | 3(8-6x)=41 | | x=(5x)-30 | | 5(2-3y)-15=2y-3 | | -12x-35=10-7x | | 45+15x=x | | 7n+3=-3n+27 | | 2.7p+4.03-.27=-8.93 | | 10x-20-8x/3 | | 2(p+6)=80 | | -2(-x+1)=23+7x | | -x+3+x=x-(x-3) | | -6(1-2x)=-102 | | B+11=-21 | | 7x-4+x=2 | | 10x+20=150 | | 4x+6=72 | | 3y-23=-43+8y |

Equations solver categories